Teknologi Kinetik Penggunaan Properti Fan pada Komunitas Malang Fire Dance - Riza Andini; Robby Hidajat (Gesture: Jurnal Seni Tari, 2026)
This study explores the application of kinetic technology through the use of fan properties in the Malang Fire Dance Community in Malang City. The purpose of this research is to analyze how body movement energy is applied in fire dance performances and how the integration between the body, space, and props creates performance aesthetics. This study employs a qualitative method with a phenomenological approach, in which the researcher was directly involved in observation, interviews, and documentation in the field. Data analysis was carried out using Laban Movement Analysis (LMA) theory, which consists of four main components: Body, Effort, Shape, and Space. The results show that the fan functions as the main medium to visualize kinetic energy through coordinated body movements, balanced use of force and timing, aesthetic fire visual forms, and the dancers’ spatial awareness within the performance space. Kinetic technology in fire dance serves not only to produce visual beauty but also as a synergy between science (motion energy) and art (body expression), resulting in performances that are safe, dynamic, and aesthetically engaging.